Pengaruh Pengalaman Auditor Terhadap Kualitas Audit Dimoderasi Penerapan Teknologi Informasi - Meirafiska Kurnia Raharja; Rida Perwita Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of auditor experience on audit quality moderated by the application of information technology. The subjects of this study were auditors from public accounting firms (KAP) holding registered CPAs in Indonesia listed in the 2023 IAPI Directory, with the object of research on competence, auditor experience, audit quality, and application of information technology. The population in this study amounted to 3276 lists of CPA holders in Indonesia listed in the 2023 IAPI Directory. Determination of the sample in this study using Probability sampling technique by selecting simple random sampling technique. The number of samples needed for this study were 97 respondents. The type of data used in this study is primary data. The data analysis method in this study uses the Partial Least Square (PLS) approach using the WarpPls 8.0 analysis tool. The results of this study found that auditor experience has a significant effect on audit quality. The application of information technology cannot moderate the effect of auditor experience on audit quality.